(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research identifies the driving factors and barriers in implementing ethical marketing to build global brand loyalty. Using a systematic literature review (SLR) approach with PRISMA methodology, this research analyzes 21 related articles of ethical marketing, which includes regulatory pressure, customer awareness, high costs, and cultural differences as key factors. These findings provide practical insights for global companies in optimizing ethical marketing strategies to increase brand loyalty in diverse global markets.